MAYBE Initial complexity problem: 1: T: (?, 1) f2(a, b) -> f2(a - 1, b) [ a >= 1 ] (1, 1) f0(a, b) -> f2(c, b - 1) [ b >= 1 ] (?, 1) f2(a, b) -> f2(c, b - 1) [ b >= 1 /\ 0 >= a ] start location: f0 leaf cost: 0 A polynomial rank function with Pol(f2) = V_2 Pol(f0) = V_2 orients all transitions weakly and the transition f2(a, b) -> f2(c, b - 1) [ b >= 1 /\ 0 >= a ] strictly and produces the following problem: 2: T: (?, 1) f2(a, b) -> f2(a - 1, b) [ a >= 1 ] (1, 1) f0(a, b) -> f2(c, b - 1) [ b >= 1 ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 1 /\ 0 >= a ] start location: f0 leaf cost: 0 Applied AI with 'oct' on problem 2 to obtain the following invariants: For symbol f2: X_2 >= 0 This yielded the following problem: 3: T: (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (1, 1) f0(a, b) -> f2(c, b - 1) [ b >= 1 ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c, b - 1) [ b >= 1 ] with all transitions in problem 3, the following new transitions are obtained: f0(a, b) -> f2(c - 1, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] We thus obtain the following problem: 4: T: (1, 2) f0(a, b) -> f2(c - 1, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 1, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 ] with all transitions in problem 4, the following new transitions are obtained: f0(a, b) -> f2(c - 2, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] We thus obtain the following problem: 5: T: (1, 3) f0(a, b) -> f2(c - 2, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 2, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 ] with all transitions in problem 5, the following new transitions are obtained: f0(a, b) -> f2(c - 3, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] We thus obtain the following problem: 6: T: (1, 4) f0(a, b) -> f2(c - 3, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 3, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 ] with all transitions in problem 6, the following new transitions are obtained: f0(a, b) -> f2(c - 4, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] We thus obtain the following problem: 7: T: (1, 5) f0(a, b) -> f2(c - 4, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 4, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 ] with all transitions in problem 7, the following new transitions are obtained: f0(a, b) -> f2(c - 5, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] We thus obtain the following problem: 8: T: (1, 6) f0(a, b) -> f2(c - 5, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 5, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 ] with all transitions in problem 8, the following new transitions are obtained: f0(a, b) -> f2(c - 6, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] We thus obtain the following problem: 9: T: (1, 7) f0(a, b) -> f2(c - 6, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 6, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 ] with all transitions in problem 9, the following new transitions are obtained: f0(a, b) -> f2(c - 7, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] We thus obtain the following problem: 10: T: (1, 8) f0(a, b) -> f2(c - 7, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 7, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 ] with all transitions in problem 10, the following new transitions are obtained: f0(a, b) -> f2(c - 8, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] We thus obtain the following problem: 11: T: (1, 9) f0(a, b) -> f2(c - 8, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 ] (1, 9) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 8, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 ] with all transitions in problem 11, the following new transitions are obtained: f0(a, b) -> f2(c - 9, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 8 ] We thus obtain the following problem: 12: T: (1, 10) f0(a, b) -> f2(c - 9, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 ] (1, 10) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 8 ] (1, 9) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 9, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 ] with all transitions in problem 12, the following new transitions are obtained: f0(a, b) -> f2(c - 10, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 9 ] We thus obtain the following problem: 13: T: (1, 11) f0(a, b) -> f2(c - 10, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 ] (1, 11) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 9 ] (1, 10) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 8 ] (1, 9) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 10, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 ] with all transitions in problem 13, the following new transitions are obtained: f0(a, b) -> f2(c - 11, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 10 ] We thus obtain the following problem: 14: T: (1, 12) f0(a, b) -> f2(c - 11, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 ] (1, 12) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 10 ] (1, 11) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 9 ] (1, 10) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 8 ] (1, 9) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 11, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 ] with all transitions in problem 14, the following new transitions are obtained: f0(a, b) -> f2(c - 12, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 11 ] We thus obtain the following problem: 15: T: (1, 13) f0(a, b) -> f2(c - 12, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 ] (1, 13) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 11 ] (1, 12) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 10 ] (1, 11) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 9 ] (1, 10) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 8 ] (1, 9) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 12, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 ] with all transitions in problem 15, the following new transitions are obtained: f0(a, b) -> f2(c - 13, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 12 ] We thus obtain the following problem: 16: T: (1, 14) f0(a, b) -> f2(c - 13, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 ] (1, 14) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 12 ] (1, 13) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 11 ] (1, 12) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 10 ] (1, 11) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 9 ] (1, 10) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 8 ] (1, 9) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 13, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 ] with all transitions in problem 16, the following new transitions are obtained: f0(a, b) -> f2(c - 14, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ c - 13 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 13 ] We thus obtain the following problem: 17: T: (1, 15) f0(a, b) -> f2(c - 14, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ c - 13 >= 1 ] (1, 15) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 13 ] (1, 14) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 12 ] (1, 13) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 11 ] (1, 12) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 10 ] (1, 11) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 9 ] (1, 10) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 8 ] (1, 9) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 By chaining the transition f0(a, b) -> f2(c - 14, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ c - 13 >= 1 ] with all transitions in problem 17, the following new transitions are obtained: f0(a, b) -> f2(c - 15, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ c - 13 >= 1 /\ c - 14 >= 1 ] f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ c - 13 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 14 ] We thus obtain the following problem: 18: T: (1, 16) f0(a, b) -> f2(c - 15, b - 1) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ c - 13 >= 1 /\ c - 14 >= 1 ] (1, 16) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ c - 13 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 14 ] (1, 15) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ c - 12 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 13 ] (1, 14) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ c - 11 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 12 ] (1, 13) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ c - 10 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 11 ] (1, 12) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ c - 9 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 10 ] (1, 11) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ c - 8 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 9 ] (1, 10) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ c - 7 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 8 ] (1, 9) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ c - 6 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 7 ] (1, 8) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ c - 5 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 6 ] (1, 7) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ c - 4 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 5 ] (1, 6) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ c - 3 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 4 ] (1, 5) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ c - 2 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 3 ] (1, 4) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ c - 1 >= 1 /\ b - 1 >= 1 /\ 0 >= c - 2 ] (1, 3) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ c >= 1 /\ b - 1 >= 1 /\ 0 >= c - 1 ] (1, 2) f0(a, b) -> f2(c', b - 2) [ b >= 1 /\ b - 1 >= 0 /\ b - 1 >= 1 /\ 0 >= c ] (b, 1) f2(a, b) -> f2(c, b - 1) [ b >= 0 /\ b >= 1 /\ 0 >= a ] (?, 1) f2(a, b) -> f2(a - 1, b) [ b >= 0 /\ a >= 1 ] start location: f0 leaf cost: 0 Complexity upper bound ? Time: 2.592 sec (SMT: 2.416 sec)